Efeito da radiofrequência não ablativa aplicada em tecido vulvovaginal de mulheres com incontinência urinária de esforço - Lucchesi, Fabiana Duarte Fonseca (2023)
Stress Urinary Incontinence (SUI) is a global public health problem that affects women of all ages, causing deterioration in physical and mental health. Non-ablative radiofrequency (RF) applied to vulvovaginal tissue generates a thermal effect with consequent neocollagenesis and neoelastogenesis. The improvement in tissue tightness and collagen quality contributes to the urethral closure mechanism. Therefore, the aim was to develop a protocol with non-ablative RF technology applied to vulvovaginal tissue to minimize the frequency and volume of urinary leakage in women with SUI. For this original clinical study, longitudinal research with a descriptivequantitative approach was carried out. Participants included 19 women diagnosed with SUI who received six treatment sessions with non-ablative RF applications in vulvovaginal tissue in the urethral meatus with an interval of one week between each application. Assessments were carried out before and after treatment, and assessment instruments with objective measures were used (ICIQ-UI SF, FSFI, one-hour Pad Test, Clinical Perina and a Satisfaction Questionnaire). No adverse events or side effects were observed. The results with treatment with the Biomedical Protocol developed in this piece of research demonstrated statistical significance in minimizing the volume and frequency of urinary loss and improving sexual function. Urinary loss in the onehour Pad Test decreased after treatment from 99.69 g before treatment to 19.80 g after treatment, and 95% of the participants showed a reduction in the volume of urine loss in the one-hour Pad Test. Of the 19 women participating in this study, 100% showed a decrease in their final post-treatment ICIQ-UI SF scores. The outcome of the Desire, Excitement and Orgasm domains demonstrated a significant increase of (α = 5%), as well as the total FSFI score, which showed an increase of 3,30 points. The use of nonablative RF on vulvovaginal tissue induces neocollagenesis, neoelastogenesis, neoangiogenesis and neurogenesis, in addition to improving the mechanical resistance of the vulvovaginal tissue and tissue laxity. The results demonstrated that the effects of non-ablative RF technology applied to the urethral meatus reduce the frequency and volume of urinary loss in women with SUI and have a positive impact on the woman’s quality of life, as 78,9% of the volunteers (15) “Totally Agreed” or “Agreed’ that they were satisfied with the results of the protocol. The present study suggests the potential use of non-ablative RF to minimize the frequency, volume, and impact of urinary leakage in women with SUI.